Modifikasi proses pengolahan Boiler Feed Water (BFW) dari All Volatile Treatment (AVT) menjadi Oxygenated Treatment (OT) untuk produksi listrik ramah lingkungan - Sigit Setyawan; Ilham Satria Raditya Putra; Agik Dwika Putra; Rochim Bakti Cahyono (Jurnal Rekayasa Proses, 2021)
In power plant industries, boiler feed water (BFW) quality becomes the main parameter for steam generation, which is used for electricity production. To generate standard BFW for power plants, each impurity within water resources should be removed to prevent corrosion and scale deposition by several processes such as sedimentation, coagulation, polishing, and deaeration. Operation conditions that involved high temperature would trigger corrosion as a crucial factor in the maintenance and practical lifetime of the equipment. In the beginning of the operation, PT. Cirebon Electric Power (CEP) used All Volatile Treatment–Reduction (AVT-R) by injection of both ammonia and hydrazine. In order to optimize the operation, the BFW treatment was changed to All Volatile Treatment–Oxidation (AVT-O) that only uses of ammonia and deaerator for removing the dissolved gas. Based on the actual evaluation, AVT technology showed less performance related to corrosion prevention and high chemical consumption. Therefore, PT. CEP tried to implement modification in the BFW treatment, which is AVT technology to Oxygenated Treatment (OT). This paper is to evaluate the effect of those modifications on corrosion prevention and resource-energy saving. The modification into OT showed valuable results that decrease concentration of dissolved Fe from 1 ppb to 0.1 ppb in the deaerator outlet stream. This data reveals that good corrosion prevention can be achieved through the creation of passive layers, hematite Fe2O3. Oxygen injection into the water circulation system yielded an oxidation atmosphere so that the passive layer, Fe2O3, was formed. In addition to corrosion prevention, this modification also cut the amount of ammonia injection into the system from 2 ppm to 0.12 ppm. Reduction of that ammonia injection provides other benefits such as decreasing the volume of resin regeneration, which becomes only twice a month. This situation also created other benefits such as reducing the regeneration water, chemicals, and wastewater. Thus, the modification could establish the electricity production by PT. CEP more environmentally friendly and sustainable.